2011
DOI: 10.1292/jvms.10-0438
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Aloe Vera Oral Administration on Cutaneous Wound Healing in Type 2 Diabetic Rats

Abstract: ABSTRACT. Delayed wound healing is one of the complications of diabetes mellitus. The present study was performed to investigate the effect of Aloe vera oral administration on open wounds in type 2 diabetic rats. Full thickness open wounds (1.5  1.5 cm) were created under general anesthesia on the backs of the rats. These rats were divided into two group, a control group (Group C) and an Aloe vera oral administration group (Group A). Each wound area was measured on days 1, 2, 4 and 8 postwounding. The stages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(49 citation statements)
references
References 28 publications
2
42
0
1
Order By: Relevance
“…Among these ayurvedic drugs, the wound healing activities of Aloe vera were extensively investigated in the in vivo and in vitro studies. In the in vivo diabetic rats study, Atiba et al (2010) showed that oral administration of Aloe vera aqueous extract to diabetic rats with wound at the back produced a significant wound healing effect (p < 0.05). Despite our formula NF3 and Aloe vera extract both exhibited wound healing properties, the effective dose of NF3 (980 mg/kg) used was higher than that of Aloe vera extract (∼100 mg/kg).…”
Section: Discussionmentioning
confidence: 99%
“…Among these ayurvedic drugs, the wound healing activities of Aloe vera were extensively investigated in the in vivo and in vitro studies. In the in vivo diabetic rats study, Atiba et al (2010) showed that oral administration of Aloe vera aqueous extract to diabetic rats with wound at the back produced a significant wound healing effect (p < 0.05). Despite our formula NF3 and Aloe vera extract both exhibited wound healing properties, the effective dose of NF3 (980 mg/kg) used was higher than that of Aloe vera extract (∼100 mg/kg).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that these above-mentioned activities act synergistically in the healing process itself (Velnar et al, 2009). Open cutaneous wounds remain one of the major complications of various diseases, such as diabetes and venous ulcers (Abu-Al-Basal, 2010; Atiba et al, 2011). Because open wounds increase the vulnerability to invasion of injured tissue by microorganisms, creating a vicious cycle with subsequent devastating consequences (Kumar et al, 2007;de Fatima et al, 2008), safe and efficient wound healing agents are needed to accelerate wound closure.…”
Section: Introductionmentioning
confidence: 99%
“…This plant is used in digestive problems, asthma, peptic ulcer, skin irritation, burns, wound, eczema, acne, psoriasis, dermatitis and diabetes (Puvabanditsin and Vongtongsri, 2005;Reuter et al, 2008;Mohamed, 2011;Yagi et al, 2011). It has been demonstrated that oral administration of mucilage of A. vera to type II diabetes Wistar rat improves the trend of wound healing by increasing in the expression of vascular endothelial growth factor (VEGF) and transforming growth factor-β1 (TGF-β1) which stimulates the fibroblast for reconstruction of extracellular matrix (Atiba et al, 2011;Mirmalek et al, 2015).…”
Section: Aloe Veramentioning
confidence: 99%